2007
DOI: 10.1017/s0954579407070198
|View full text |Cite
|
Sign up to set email alerts
|

Relations of effortful control, reactive undercontrol, and anger to Chinese children's adjustment

Abstract: The purpose of the study was to examine the zero-order and unique relations of effortful attentional and behavioral regulation, reactive impulsivity, and anger/frustration to Chinese first and second graders' internalizing and externalizing symptoms, as well as the prediction of adjustment from the interaction of anger/frustration and effortful control or impulsivity. A parent and teacher reported on children's anger/frustration, effortful control, and impulsivity; parents reported on children's internalizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
89
1
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(113 citation statements)
references
References 105 publications
(115 reference statements)
15
89
1
8
Order By: Relevance
“…Consistent with Chinese cultural values regarding the expression of anger/frustration (Markus & Kitayama, 1991) and encouragement of emotional and behavioral control/regulation in Chinese schools (Phelps, 2005), high temperamental susceptibility to anger showed a persistent positive relation to externalizing. The results are similar to those with Euro-American samples (e.g., Eisenberg et al, 2001;Eisenberg, Shepard, Fabes, Murphy, & Guthrie, 1998;Zahn-Waxler, Cole, Richardson, & Friedman, 1994) and extended the cross-sectional findings on Chinese children (Eisenberg et al, 2007;Zhou et al, 2004).…”
Section: The Prospective and Unique Relations Of Parenting Styles Andsupporting
confidence: 87%
See 2 more Smart Citations
“…Consistent with Chinese cultural values regarding the expression of anger/frustration (Markus & Kitayama, 1991) and encouragement of emotional and behavioral control/regulation in Chinese schools (Phelps, 2005), high temperamental susceptibility to anger showed a persistent positive relation to externalizing. The results are similar to those with Euro-American samples (e.g., Eisenberg et al, 2001;Eisenberg, Shepard, Fabes, Murphy, & Guthrie, 1998;Zahn-Waxler, Cole, Richardson, & Friedman, 1994) and extended the cross-sectional findings on Chinese children (Eisenberg et al, 2007;Zhou et al, 2004).…”
Section: The Prospective and Unique Relations Of Parenting Styles Andsupporting
confidence: 87%
“…As one of the first longitudinal studies on parenting, temperament, and Chinese children's behavior problems (e.g., Chen, Liu, & Li, 2000;Chen et al, 2002), this study extended the previous research with this population (which was mostly cross-sectional and/or did not simultaneously include both parenting and temperament as predictors of adjustment, e.g., Chen et al, 2002;Eisenberg et al, 2007;Nelson et al, 2006;Porter et al, 2005). The most important findings are the prospective and unique relations of authoritative and authoritarian parenting and temperamental anger/frustration to Chinese children's externalizing problems, which provided evidence for the generalization of socialization and temperament models for externalizing problems to the Chinese culture.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Epidemiological findings suggested that Hong Kong Chinese children face the same kind of developmental and mental health challenges as those faced by children in the West (Leung et al 2008). Eisenberg and colleagues found that Chinese and U.S. children have similar patterns of effortful control and emotionality (Zhou et al 2004;Eisenberg et al 2007). On the other hand, in studies on cultural variation in emotional expression, it was found that Chinese and other Asians tended to dampen their emotional expressions in the interests of maintaining group harmony (Tsai et al 2002).…”
Section: The Sel Situation In Hong Kongmentioning
confidence: 99%
“…These teachers usually teach major subjects in class, and they are also responsible for taking care of the students in their classes (Eisenberg et al 2007). In the present study, the class teachers implemented the PATHS in two of the schools, while in the other school, the SGT taught PATHS to all the first grade classes.…”
Section: Mode and Level Of Implementationmentioning
confidence: 99%